2020
DOI: 10.3390/biom10040645
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein Cholesterol in Age-Related Ocular Diseases

Abstract: There is limited understanding of the specific role of high-density lipoprotein cholesterol (HDL-C) in the development of various age-related ocular diseases, despite it being a common measurable biomarker in lipid profiles. This literature review summarizes current knowledge of the role of HDL-C, if any, in pathogenesis and progression of four age-related ocular diseases, namely age-related macular degeneration (AMD), age-related cataract, glaucoma, and diabetic retinopathy (DR), and will primarily discuss ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 142 publications
1
12
0
Order By: Relevance
“…However, several studies have shown that age-related macular degeneration, a leading cause of irreversible vision loss, is positively associated with HDL-C, although conflicting results have remained. [26][27][28] A forest plot in the meta-analysis by Wang et al 26 showed a significant association between HDL-C and age-related macular degeneration, suggesting that people with high HDL-C levels may be at increased risk for age-related macular degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have shown that age-related macular degeneration, a leading cause of irreversible vision loss, is positively associated with HDL-C, although conflicting results have remained. [26][27][28] A forest plot in the meta-analysis by Wang et al 26 showed a significant association between HDL-C and age-related macular degeneration, suggesting that people with high HDL-C levels may be at increased risk for age-related macular degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…MIR4453HG is an IncRNA gene and located nearby some risk genes that have been reported to be associated with blood protein level (gene ARFIP1 48 ) and lipoprotein cholesterol levels (gene TRIM2 49 ). Both traits are highly relevant to the risk for type 2 diabetes 50,51 and cataract 52,53 . KCNK17 encoded a protein in the family of potassium channel 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Tangier disease (OMIM# 205400) is caused by recessive mutations in ABCA1, and is characterized by hypoalphalipoproteinemia (low serum ApoA1-HDL levels), mild neuropathy, atherosclerosis, retinopathy, corneal infiltrates and scarring, lipid deposits in the conjunctiva, and cataract formation (29). [The reader is referred to a recent review that provides detailed analysis of the specific role of HDL in age-related retinopathies (30).] This review discusses the role of sterol efflux in retinal physiology and pathophysiology.…”
Section: General Considerations: Cholesterol Synthesis Uptake and Ementioning
confidence: 99%